Persistence of insecticidal activity of novel bio-encapsulated formulations of Bacillus thuringiensis var. kurstaki against Choristoneura rosaceana [Lepidoptera: Tortricidae] - Côté, J.-C.; Vincent, C.; Son, K.-H.; Bok, S. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2001)
DiPelTM, a registered Bacillus thuringiensis var. kurstaki (Btk)-based formulation, and experimental bio-encapsulated Btk formulations were sprayed in an apple orchard. Their persistence was assessed in the laboratory against obliquebanded leafroller (Choristoneura rosaceana) larvae for three consecutive years. In 1995, DiPel and the bio-encapsulated formulation caused significantly higher larval mortality than the control at least 1 day, and up to 27 days after treatments, respectively. In 1996, although 6.4 mm of rain fell during the day of treatments, DiPel and the bio-encapsulated formulation caused respectively 21 and 33% larval mortality immediately after treatments. DiPel caused significantly higher mortality than the control for up to 3 days while the bio-encapsulated formulation caused significantly higher mortality for up to 14 days. In 1997, two Btk strains (HD-1 and BMP123) were sprayed at different concentrations in a.i. (3 and 8%) and doses (30 and 240 g 15 L-1 applied). Higher concentrations of a.i. in the Btk formulations and higher doses sprayed increased the persistence of the insecticidal activity. Among the meteorological factors that were measured (i.e. precipitations, temperature and solar radiations), precipitations reduced the persistence of the insecticidal activity. Solar radiations may have modulated the persistence of the formulations.